1958
DOI: 10.1039/tf9585401754
|View full text |Cite
|
Sign up to set email alerts
|

The spaces in a uniform random suspension of fibres

Abstract: The distribution of spaces in a random network of straight fibres is considered, such as might be occupied by a spherical object pIaced within the network or might allow free rotation to an elongated one. The approximate treatment of a network of flexible fibres is discussed briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
644
2
5

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,055 publications
(670 citation statements)
references
References 0 publications
19
644
2
5
Order By: Relevance
“…Solute behavior in hydrogels has been explained in terms of reduction in hydrogel free volume [20,21,22], enhanced hydrodynamic drag on the solute [23,24], increased path length due to obstruction [25,26], and a combination of hydrodynamic drag and obstruction effects [27].…”
Section: Amsden's Obstruction Scaling Theorymentioning
confidence: 99%
“…Solute behavior in hydrogels has been explained in terms of reduction in hydrogel free volume [20,21,22], enhanced hydrodynamic drag on the solute [23,24], increased path length due to obstruction [25,26], and a combination of hydrodynamic drag and obstruction effects [27].…”
Section: Amsden's Obstruction Scaling Theorymentioning
confidence: 99%
“…Surprisingly enough, this very basic problem still draws some intense discussions in the electrophoresis community [143,144]. Traditionally the Ogston-Morris-Rodbard-Chrambach (OMRC) [145][146][147] model of gel electrophoresis is the central paradigm in this regime. The basic assumption of this model is that the scaled mobility m*, i.e., the ratio between the mobility m in the separation media and the free-solution mobility m 0 , is equal to the fraction f of the volume available to the particle (without violating the condition of volume exclusion with the media):…”
Section: Ogston Sievingmentioning
confidence: 99%
“…To estimate the available volume, it is common to use an early result of Ogston [145], sometimes with correction terms. Using geometrical and statistical arguments, Ogston showed that the fractional volume available to a spherical particle in a random array of infinitely long (but not cross-linked) fibers is given by…”
Section: Ogston Sievingmentioning
confidence: 99%
“…The strong lowering of the critical temperatures with increasing surfactant concentration could be due to transient cross-linking of adjacent micelles by the PEG molecules, but this is unlikely since oxyethylene-water interaction still strongly dominates over oxyethylene self-interaction at 60°C. A comparison of the surfactant consolution boundary in water and in aqueous PEG solutions ( fig.2) indicates that a simple excluded volume effect does not explain the data [27]. We propose that the PEG effect is due to an unfavourable configurational (entropic) effect between the micelles and the PEG molecules, i.e.…”
Section: The Effect Of Polyethylene Glycol4000mentioning
confidence: 83%